Implementation of Objective Matrix and Root Cause Analysis for Productivity Analysis PT. Indomarco Adi Prima SP Deket Lamongan - Fikri, Ali Zian; Widada, Dharma; Fathimahhayati, Lina Dianati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT Indomarco Adi Prima Stock Point Deket Lamongan is one of the business units of PT Indofood Sukses Makmur Tbk, which distributes consumer products. The company has 300 outlets in grocery stores and modern stores with a distribution target of 30 outlets for each salesman in a day. However, in its implementation, the target is only sometimes achieved. Other problems, such as product delivery errors and delivery delays, occur frequently. This research aims to analyze the company’s productivity level using the Objective Matrix (OMAX) method. Productivity measurement also involves the Analytical Hierarchy Process (AHP) method in determining the weight of each ratio. Based on the calculation of productivity during the measurement period from January 2022 to December 2022 using Objective Matrix (OMAX), the results obtained are productivity index values that decreased during the measurement period, namely February (-4,75%), March (-3.90%), May (-17.48%), June (-11.92%), July (-31.28%), and October (-7.04%). Then, based on the results of productivity indicator analysis, it is known which ratio indicator has the lowest value and causes the productivity index to fall, namely ratio 1, ratio 2, ratio 5, ratio 6, and ratio 7. The decrease in productivity index based on Root Cause Analysis (RCA) using fishbone diagram tools due to no heat reducer, no computer and truck maintenance schedule, less communication between employees, travel time estimation is not good, attendance system updates are not carried out, limited warehouse area, high work intensity, no instructions for the preparation of goods in the warehouse area, stock goods arrive late, rainy season, road repairs, no periodic checks, and unpredictable road conditions.